Analyzing Factors Influencing Concertgoers on Revisit Intention at Online Music Concert Using PERVAL Framework (The Indonesian Journal of Business Administration, 2021)
The music industry is one of the industries that contributes the most to the country’s GDP, contributed 8% in 2017 and contributed to the creative economy GDP of IDR 4.89 trillion. Concerts or festivals are one of the crucial mediums for the development of the music industry. Due to the COVID-19 pandemic, causing a decline in the music industry. There were 113 concerts, tours, and music festivals that were delayed as of April 2020, currently around 50,000 creative workers in the music festival event industry are in danger of losing their jobs, and 1,218 organizers throughout Indonesia, the minimum potential loss obtained is IDR 2.69 trillion and a maximum of IDR 6.94 trillion. This causes event promoters and musicians must adapt to the current conditions that prohibit crowds of people, by holding online music concert. Based on the problem, this research aims to analyze factors influencing concertgoers willing to move from live music concert to online music concert and revisit intention at online music concert.There are several related theories in this research, including PERVAL framework. It showed that perceived value is a strong indicator and positively influences future purchase intentions or behaviour. This research used a quantitative method by using questionnaire to collect the data via Google Forms. The data was distributed to 200 respondents who have attended online music concert. There are several other variables in this research, which are satisfaction, loyalty, and motivation.The data is processed using SmartPLS 3 software to conduct a Path Analysis. The findings show that emotional value, social value, quality value, and price value significantly influence satisfaction. Satisfaction and loyalty significantly influence revisit intention at online music concert. But motivation variable does not have a significant value on revisit intentions at online music concert. Keywords: PERVAL Framework, Satisfaction, Loyalty, Motivation, Revisit Intention, Online Music Concert